Perioperative Endocarditis Management in a Patient with Homozygous Sickle Cell Disease - Gozdzik, Malgorzata; Mariotti, Sergio; Genoni, Michele; Zientara, Alicja (The Thoracic and Cardiovascular Surgeon Reports, 2019)
Background Homozygous sickle cell disease (SCD) compounded with bacterial endocarditis makes open-heart surgery a multidisciplinary challenge.Case description A 45-year-old African male patient with homozygous SCD presented with right heart decompensation, tricuspid regurgitation, and endocarditis of the aortic valve. Blood coulters were positive for coagulase-negative staphylococci. An emergent double valve replacement was successfully performed involving a multidisciplinary team.Conclusion Homozygous SCD is associated with an increased risk of preoperative vaso-occlusive complications. Surgery with cardiopulmonary bypass can be performed, if hypothermia, hypoxia, acidosis, or low-flows are being avoided. Due to the lack of data, the adequate approach is still intuitive and requires standardization.
Keywords: sickle cell disease; cardiopulmonary bypass; endocarditis; sickle crisis; hemofiltration